Efektivitas Diklat Di Tempat Kerja (DDTK) Analisis Jabatan di Kantor Kementerian Agama Kota Magelang - Suyadi, Suyadi (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
Training in the workplace (DDTK) on job Analysis is a policy that must be undertaken by government apparatus; either they are positioned in central or regional level. DDTK on Job Analysis is increasingly required especially after the performance benefits were being paid to the employees within the Ministry of Religious Affairs. The benefit necessitates employees to describe their work targets which will be used as the determinant for their position/level.  DDTK on Job Analysis in the Ministry of Religious Affairs at Magelang Regency has given positive values for the employees towards the understanding of the Job Analysis considering that, before the training, there were lots of employees who did not comprehend the concept. This was evidenced by the result of the pre-test conducted in advance to the training. Organizing DDTK on Job Analysis has provided real contribution among the employees of the Ministry of Religious Affairs at Magelang Regency in terms of their understanding on Job Analysis as well as their improved competence in arranging the Job Analysis. Keywords: Analysis Of Position, Employees Working Objectives, DDTK